-14=.4(9-2b)

Simple and best practice solution for -14=.4(9-2b) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14=.4(9-2b) equation:


-14=.4(9-2b)

We simplify the equation to the form, which is simple to understand
-14=.4(9-2b)

Reorder the terms in parentheses
-14=+(+3.6-0.8b)

Remove unnecessary parentheses
-14=+3.6-0.8b

We move all terms containing b to the left and all other terms to the right.
+ 0.8b=+3.6+14

We simplify left and right side of the equation.
+ 0.8b=+17.6

We divide both sides of the equation by 00.8 to get b.
b=22

See similar equations:

| 12.51-4.3a=24.25 | | 11x-1+24=12x+3 | | f(-4)=3x+7 | | x^2+6x+9=18 | | 1.8r+9=5.7t-6 | | 6u+26=8u | | x^2+9x+50=0 | | 19x+12y-5x+13y+75= | | 4=4.5(4y-2) | | 3x+2x+1=4+8x | | 8x+7x=-27 | | 3(2c-5)-4(2-c)=3(4c-5) | | 5x+12=6+3x | | 4(5-2x)+6+2x= | | -(12-4x)+8(10-x)=x | | 2x^2=182 | | 14=10+2n | | 4x+7+x=3(x-1) | | 36x+2=0 | | 10x-15=0 | | 49b^3-4b=0 | | 4y+2=6(8y-7) | | 17p+10+52q+13p-2q= | | 8-4(2-5x)-3(2x-3)=9+14x | | 2x-(5x+5)=3x-17 | | x/5+7=18 | | 15=-2(2T+1) | | 6y+2=3(3+2y) | | n-10+8n+3= | | 7x^2+7x-6=0 | | 3(1-2b)+5(7b-8)=50 | | 3a-1=14-2a |

Equations solver categories